Job Mobility along the Technological Ladder : A Case Study of Australia - Cezary A. Kapuscinski; P. N. (Raja) Junankar; Xin Meng (Institute for the Study of Labor (IZA), 2004)
Labour economists have been increasingly interested in the impact of technological change upon employment and unemployment. However, the predominant focus of empirical studies has been on employment and unemployment stocks, whereas technological change is more likely to affect the flows of labour. This paper focuses on the latter issue. In particular, given the technological change, two major questions posed in this paper are: (i) who moves from low-tech to high-tech jobs and who moves from high-tech to low-tech jobs, and (ii) what are the factors which drive such movements. The data used in this study are from the 1994 Australian Labour Mobility Survey. A new index describing the technological level of a job is constructed and the magnitude and direction of movements along the technological ladder are examined. Using individual-level socio-economic variables, we explain the determinants of the direction of the job change. Some relevant policy implications are also discussed.
Keywords: J62; J63; O33; 330; job mobility; technological ladder; employment and unemployment flows; Arbeitsmobilität; Technischer Fortschritt; Hochtechnologiesektor; Schätzung; Sektorale Beschäftigungsstruktur; Australien